Atitudes dos consumidores sobre o jeanswear: diferenças entre a geração Z e os baby boomers - Gomes, Onnara Custódio (2018)
Attitude is a construct composed of cognitive, affective and conative elements, where individuals develop an evaluative answer, favorable or not, in relation to a product. The objective of this research was to evaluate the differences in the attitudes of Generation Z consumers, in relation to Baby boomers, regarding jeanswear. This was a descriptive, cross-sectional and with quantitative approach research, developed on the internet, with a non-probabilistic sample and application of convenience sampling. An on-line questionnaire was used as an instrument to collect the data. The valid sample size of the survey was 373 respondents, 230 of Generation Z and 143 of the Baby boomers. Based on the results, it was verified that the higher number of participants of the research was of Generation Z, with predominance of feminine gender in both generations; 40% of Generation Z and only 19.6% of Baby boomers already participated in fashion research and 95.7% of Generation Z and 96.5% of Baby boomers never participated in research on jeanswear; both generations consume denim pieces eventually; Generation Z owns more denim pieces; in the Baby Boomers, the Cognitive Elements manifest themselves more expressively than in Generation Z, and in these the Affective Elements manifest themselves more strongly than in the Baby Boomers, and the Conative Element expresses itself less expressively than the other elements for both generations; there was a significant and positive influence of the Affective and Conative Elements with the Attitudes construct in relation to fashion consumption, but there was not a significant and positive influence of the Cognitive Elements with Attitudes in relation to fashion consumption. The results point to the justified and even expected incompatibility of opinions, convictions, context and reality between the generations analyzed here for jeanswear. It is believed that conducting this research will contribute to the expansion of knowledge in the fashion field, specifically on the jeanswear segment, as well as to provide a guide to future academic researches and strategic decisions in companies. One limitation of the study was the restricted number of participants, since two generations were analyzed. It is recommended to deepen the research by concentrating the studies by Brazilian region, among other countries and with other generations, such as X and Y.